The Impact of Social Media Marketing on Increasing Individual PPH and PNBP in Indonesia: A Systematic Literature Review - Putra, Suadi Sapta; Digdowiseiso, Kumba (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Social media marketing methods frequently incorporate promotional, sales, and branding techniques that can provide supplementary revenue for individuals and corporations. This study aims to determine the impact of social media marketing on the computation and augmentation of Individual Income Tax (PPH) in Indonesia. The literature study of this research is organized systematically to examine the influence of social media marketing on the growth of Individual Income Tax (PPH) and Non-Tax State Income (PNBP) in Indonesia. Further investigation is required to comprehend the impact of firm marketing strategies in the digital domain on Individual PPH and its contribution to PNBP. To effectively address the challenges posed by the digital economy, the government and business entities must collaborate in formulating tax laws that are adaptable and efficient.